2023
DOI: 10.1111/psyg.13037
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization in cancer survivors: an updated systematic review and meta‐analysis for quantitative studies

Cian‐Cian Lin,
Yu‐Ning Her

Abstract: BackgroundDemoralization can cause impairments across all life aspects of cancer patients. Cancer patients are also vulnerable during their survivorship. The purpose of this review is to examine the risk of demoralization and associated risk factors among cancer survivors who have completed their primary anti‐cancer treatment or time since diagnosis ≥5 years without recurrence.MethodsWe searched databases of PubMed, Cochrane, Embase, PsycINFO and ClinicalTrial.gov to identify eligible studies which reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Here, the findings for an effect of age on demoralization were mixed, showing either no association (39), a positive relationship (40) or a negative correlation (36,41,42) between age and demoralization, which might be influenced by treatment status (41). However, a recent meta-analysis including cancer patients with a mean age between about 50 and 68 years, and thus potentially biased by rather older participants, identified age as a risk factor for demoralization (43). This leads to the suggestion that the magnitude and directionality of an age effect on demoralization in cancer likely depend on the included agegroups.…”
Section: Discussionmentioning
confidence: 71%
“…Here, the findings for an effect of age on demoralization were mixed, showing either no association (39), a positive relationship (40) or a negative correlation (36,41,42) between age and demoralization, which might be influenced by treatment status (41). However, a recent meta-analysis including cancer patients with a mean age between about 50 and 68 years, and thus potentially biased by rather older participants, identified age as a risk factor for demoralization (43). This leads to the suggestion that the magnitude and directionality of an age effect on demoralization in cancer likely depend on the included agegroups.…”
Section: Discussionmentioning
confidence: 71%
“…In mainland China, clinicians often conflate demoralization with depression, but unlike the lack of pleasure in depression, patients with demoralization syndrome can still experience happiness. Reports suggest that demoralization is more common than depression in cancer patients and more closely associated with suicidal intentions (31,32). The systematic review of Lin et al indicated that about 25.98% of cancer survivors experience demoralization, with breast cancer patients scoring higher than others (32).…”
Section: Demoralizationmentioning
confidence: 99%
“…Reports suggest that demoralization is more common than depression in cancer patients and more closely associated with suicidal intentions (31,32). The systematic review of Lin et al indicated that about 25.98% of cancer survivors experience demoralization, with breast cancer patients scoring higher than others (32). A cross-sectional study in China found that over half of the patients in Xiamen showed signs of demoralization which may be related to living standards, family income, etc.…”
Section: Demoralizationmentioning
confidence: 99%